Predictors of Mortality of Asphyxiated Neonates Admitted in a Tertiary Care Hospital - Shirin, Mahfuza; Haque, Gazi Mohammad Imranul; Hossain, M Monir (Dhaka Shishu (Children) Hospital Journal, 2021)
Introduction: Perinatal asphyxia is a severe condition with significant morbidity and mortality. It is the third leading cause of neonatal mortality in developing countries including Bangladesh. To reduce asphyxia related mortality, it is necessary to find out the responsible factors to reduce the mortality. Objectives: This study was an attempt to find out the risk factors associated with mortality due to birth asphyxia. Methods: This was a cross-sectional observational study, conducted in Department of Neonatal Medicine and NICU of Dhaka Shishu (Children) Hospital during the period of March 2016 to November 2016. Term neonates of within 24 hours of age with diagnosis of perinatal asphyxia were enrolled in this study. Demographic, intrapartum, clinical and laboratory data were recorded. The immediate outcome in terms of expired or survived were also recorded. Statistical analysis was done by SPSS 25 programme. Bivariate and multivariate analyses have been done to find out the associations of risk factors with mortality. P value, <0.05 was taken as statistically significant. Results: A total of 224 asphyxiated term neonates with a mean age of 12.64±6.82 hours were studied. Mean admission weight was 2677.01±407.71gm with male to female ratio of 1.4:1. Among them 51 (22.8%) were expired. In Bivariate analysis, home trial before hospital delivery, obstructed labour, respiratory distress, unconsciousness, abnormal muscle tone, hypothermia, prolonged CRT, SpO2 <90%, hypoglycemia, and metabolic acidosis at the time of admission were significantly associated with mortality (p<0.05). It was found, home trial before hospital delivery (p=0.009, OR 4.023, 95% CI 1.424-11.366), unconsciousness (p=0.002, OR 4.811, 95% CI 1.773-13.148), hypothermia (p=0.001, OR 4.942, 95% CI 1.858-13.148), prolonged CRT (p=0.009, OR 3.651, 95% CI 1.384-9.630) and metabolic acidosis (p=0.018, OR 3.551, 95% CI 1.243-10.141) at the time of admission were independently affecting the mortality of asphyxiated neonates. Conclusion: This study found that the predictors of mortality of neonates with perinatal asphyxia were home trial before hospital delivery, unconsciousness, hypothermia, prolonged CRT and metabolic acidosis at the time of admission. DS (Child) H J 2019; 35(1) : 14-21